Flavonoid Compounds from the Herb of Krokot (Lygodium microphyllum) and their antioxidant activity against DPPH - Hadi Kuncoro; Kindi Farabi; Laode Rijai; Euis Julaeha; Unang Supratman; Yoshihito Shiono (Journal of Mathematical and Fundamental Sciences, 2018)
Six flavonoid compounds, kaempferol (1), quercetin (2), acacetin (3), quercetin-3-O-Î²-D-glucopyranoside (4), kaempferol-3-O-Î²-D-glucopyranoside (5), and isorhamnetin-3-O-Î²-D-glucopyranoside (6), were isolated from the methanol extract of the Lygodium microphyllum herb. The chemical structures of compounds 1-6 were identified on the basis of spectroscopic evidence and comparison with previously reported spectral data. Compounds 1-6 were isolated for first time from this plant. Their antioxidant activity against DPPH (2,2-Diphenyl-1-picrylhydrazyl) was evaluated. Among the compounds, quercetin (2) showed high antioxidant activity with IC50 values of 6.94 ± 0.03 Î¼g/mL.